Muscle fatigue and metabolic responses following three different antagonist pre-load resistance exercises - Carregaro, R.; Cunha, R.; Gomes Oliveira, C.; Brown, L. E.; Bottaro, M. (Journal of Electromyography and Kinesiology, 2013)
Preload of antagonist muscles can be achieved by reciprocal actions (RAs) or by opposing muscle actions. However, evidence concerning neuromuscular and fatigue responses are scarce.